Giulio Clovio e il tema della Resurrezione - Marcon, Susy (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
Having recently appeared on the market, the Resurrection of Christ painted on a copper oval has been traced back to a subject by Giulio Clovio, around 1569. There is the hypothesis that the painter is the same famous miniaturist, who in old age, in the service of Alessandro Farnese, met with the Flemish and Nordic, and therefore Roman, use of copper painting.